PENGARUH PELATIHAN PENGEMBANGAN DAN KOMPENSASI TERHADAP TURNOVER INTENTION (STUDI KASUS DOSEN POLITEKNIK NEGERI BENGKALIS) - Supriati Supriati (Inovbiz: Jurnal Inovasi Bisnis, 2018)
The turnover rate lowering of lecturers was caused by such efforts as the organizational commitment like training and development, compensation done by the management of Bengkalis Polytechnic to deal with problems related to turnover intention.The present research sought to find out and investigate the effect of training and development, compensation and work specification both simultaneously and partially on the turnover intention of the lecturers at Bengkalis Polytechnic to know the function of which independent variable was the most dominant to affect the turnover intention. The method was descriptive; whereas, the population included all 58 lecturers at Bengkalis Polytechnic. Using a saturated sampling technique, all population became the sample. The data were collected using a field study and library research such as observation, interview and questionnaire. To determine the degree of correlation and the effect of an independent variable on the dependent variable, a multiple linear regression model was used. The hypotheses were tested using a statistical analysis. The results show that the multiple correlation coefficient (R) was 0.799 with α > 0.05 and the determination coefficient (R2) was 58.6% meaning that 58.6% of the training and development, compensation and work specification had an effect on the turnover intention of the lecturers at Bengkalis Polytechnic. The Significance effect of the training and development, compensation and work specification on the turnover intention could be indicated that the value of F count was smaller than F table at alpha level t = 5%. The results indicates that F count = 27.854 was bigger than F table = 2.5397 at significance level α smaller than 0.05.  From the calculation, null hypothesis was rejected meaning that training and development, compensation, and work specification had a significant effect on the turnover intention of the lecturers at Bengkalis Polytechnic. Partial test indicates that t – value of training and development variable was 3.670, professional variable was 3.39. This indicated that training and development and compensation had an effect on turnover intention of the lecturers.